Microstructural study of MMC layers produced by combining wire and coaxial WC powder feeding in laser direct metal deposition. (March 2016) - Li, Fuquan; Gao, Zhenzeng; Li, Liqun; Chen, Yanbin
Abstract: Combined wire and powder deposition by laser (WPDL) has proven to be a promising method for fabricating Metal Matrix Compounds (MMC). Here we demonstrate the deposition of a MMC layer onto Ti6 Al4 V substrate by WPDL. WC powder was fed from a coaxial nozzle whilst titanium wire was fed from a lateral nozzle into a laser generated melt pool. The appearance of the MMC layer was controlled by process parameters including wire feeding rate, powder feeding rate and laser power. The microstructure of these compound layers were subsequently analyzed by SEM, EDS and XRD. It has shown that compound layer are comprised of α-Ti, WC, W2 C, TiC, W and (W, Ti) C1− x phase. The W2 C phase and TiC phase was formed and distributed in titanium matrix with different shape at the different location of MMC layer. WC particles were distributed throughout the MMC layer as enforcement phase, which occurring metallic bonding with matrix. The presence of WC and TiC phase in the MMC layer enhanced its microhardness and abrasive. Highlights: MMC layer fabricated on titanium by coincident wire-powder laser deposition. Monocrystal WC powder was fed from a coaxial nozzle. Microstructure and phase identification of MMC layer. Metallic bonding occurring between WC enforcement phase and matrix. Hardness and abrasive resistance of MMC layer improved.